Prognostic value of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in intensity modulated radiation therapy for nasopharyngeal carcinoma - Jiang, Yanming (Oncotarget, 2018)
BACKGROUND: Inflammatory response markers plays an important role in tumor progression. The aim of this analysis was to evaluate whether the neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) could predict the prognosis of nasopharyngeal carcinoma(NPC). MATERIALS AND METHODS: 247 patients who underwent Intensity Modulated Radiation Therapy( IMRT )were enrolled from January 2012 and December 2012. NLR, and PLR were calculated from peripheral blood cell counts taken at pre-treatment. Optimal cutoff values of NLR and PLR were determined on the basis of receiver operating characteristic curve analysis. Overall survival (OS), progression-free survival(PFS), distant metastasis-free survival (DMFS) and loco-regional recurrence-free survival ( LRFS) rates were compared according to NLR and PLR level respectively. Multivariate analysis was performed to assess the prognostic value of NLR and PLR. RESULTS: The 5-year estimated OS, PFS, LRFS and DFS were 87.2, 77.8, 96.9, and 86.2%, respectively. Our results shows that the NLR was significantly associated with T-stage (P < 0.05), N-stage (P < 0.05) and tumor stage(P < 0.05). PLR was significantly associated with T-stage (P < 0.05) and tumor stage(P < 0.05). NLR was an independent prognostic indicator for OS (HR: 3.259, P = 0.004), PFS (HR:7.093, P < 0.001), DMFS (HR: 6.576, P = 0.003), except for PLR. In subgroup analysis, adjuvant chemotherapy had no significantly improved survival for patients with high NLR. CONCLUSIONS: NLR is a strong prognostic factor for NPC patients. NLR might not be a useful indicator for selection of treatment strategies for loco-regionally advanced NPC.